Slides to Philosophy 167: Class 12 -- Newton's Early Unpublished Work in Mechanics -- Part 1. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Generally corresponds to the video segment: Class 12, Part 1.